Root Exudates Mediate the Production of Reactive Oxygen Species in Rhizosphere Soil: Formation Mechanisms and Ecological Effects - Xuqin Wang; Yalei Liu; Xiaoyan Tian; Juan Guo; Yaning Luan; Dengzhi Wang (Plants)
Reactive oxygen species (ROS), as redox messengers, play an important role in regulating plant growth, sensing biotic and abiotic stresses, and integrating different environmental signals. As the microenvironment of the interaction between root, soil and microorganism, the rhizosphere is the hotspot of ROS production and action. Root exudates are an important medium for communication between roots and the soil environment, and they have a significant regulatory effect on the production of ROS in the rhizosphere. At the same time, the formation of rhizosphere ROS is determined by the coupling of various biotic and abiotic factors, and it is also affected by environmental stresses such as temperature, humidity, and disease. This review summarizes how root exudates affect plant growth and induce plant defense mechanisms by regulating the generation and distribution of ROS. It also discusses the role of ROS in promoting the decomposition of soil organic matter, nutrient cycling, and pollutant degradation and transformation. In-depth study of the regulation mechanism of root exudates on ROS not only helps to reveal the molecular mechanism of plant adaptation to environmental stress but also provides theoretical support and practical guidance for sustainable agricultural development and ecological environment protection.